Exploring English Teachers’ Voices: Challenges in Integrating AI-Based Tools into Classroom Practices at Senior High Schools - Hanasanaturro’i, Hanasanaturro’i; Irawan, Lalu Ari; Rahman, Arif (Journal of Language and Literature Studies, 2025)
This study explores the challenges faced by English teachers in integrating artificial intelligence (AI)-based tools—such as Grammarly and conversational chatbots—into classroom practices at senior high schools. Employing a qualitative case study design, data were collected through semi-structured interviews with 15 teachers to examine institutional, technical, and socio-cultural barriers that shape AI adoption. The findings highlight three central themes. First, technical limitations emerge as a critical barrier, encompassing unstable internet connectivity, outdated hardware, and limited access to supporting infrastructure. Second, pedagogical gaps reflect teachers’ insufficient training in adapting AI tools to localized curricular demands, resulting in underutilization of available technologies. Third, cultural resistance stems from entrenched traditional teaching norms and skepticism toward technology-driven approaches, which often conflict with established classroom practices. These findings mirror broader global disparities in educational technology adoption, where systemic inequities continue to constrain digital transformation in under-resourced regions. The study emphasizes the urgency of implementing targeted interventions, including government-supported professional development programs and policy initiatives to modernize rural ICT infrastructure. By centering teacher perspectives, this research contributes to a deeper understanding of adaptation dynamics in low-resource educational contexts. Furthermore, it provides actionable insights for policymakers and practitioners seeking to reduce the urban-rural digital divide and foster more equitable integration of AI in education.